VD_FINDINFO AP / 2011 / 125 vom 21. September 2011 - VD Tribunal cantonal (2011)
CONTRAT D'ENTREPRISE, DOMMAGES-INTÉRÊTS, RÉMUNÉRATION CONVENABLE | 8 CC, 363 CO, 451 ch. 2 CPC, 452 al. 2 CPC, 405 al. 1 CPC (CH)